Humoral responses to HIVconsv induced by heterologous vaccine modalities in rhesus macaques. Issue 2 (11th March 2015) - Borthwick, Nicola J.; Rosario, Maximillian; Schiffner, Torben; Bowles, Emma; Ahmed, Tina; Liljeström, Peter; Stewart‐Jones, Guillaume E.; Drijfhout, Jan W.; Melief, Cornelis J. M.; Hanke, Tomáš
Abstract: Vaccines delivering T cell immunogen HIVconsv vectored by plasmid DNA, non‐replicating simian adenovirus and non‐replicating modified vaccinia virus Ankara (MVA) are under clinical evaluation in phase I/IIa trials in UK, Europe, and Africa. While these vaccines aim to induce effector T cell responses specific for HIV‐1, we here characterized the humoral responses induced by HIVconsv administration to macaques using six different vaccine modalities: plasmid DNA, human adenovirus serotype 5, simian adenovirus serotype 63, MVA, Semliki Forest virus replicons, and adjuvanted overlapping synthetic long peptides (SLP). We found that only the SLP formulation, but none of the genetic vaccine platforms induced antibodies recognizing linear HIVconsv epitopes, median 32/46 SLP.HIVconsv peptides. These antibodies bound to 15‐mer and SLP peptides, recombinant gp120 and trimeric gp140 of HIV‐1 Bal, YU2, JRFL, and UG037, but failed to react with HIV‐1 Bal and IIIB virions and HIV‐1 Bal‐ and IIIB‐infected human cells, and consequently failed to induce neutralizing antibodies. The HIVconsv immunogen contains conserved regions derived from Gag, Pol, Vif, and Env proteins of HIV‐1, and antibodies induced by the SLP.HIVconsv vaccination resulted in positive signals in routine HIV‐1 tests. Thus, only HIVconsv delivered by SLP resulted in seroconversion, an observation that provides important guidance for recruiting volunteers into future clinical trials. Furthermore, our data confirms that vaccine delivery by SLP induces humoral as well as cellular immune responses and could be considered for inclusion in future vaccine regimens where this is required. Abstract : The humoral immune response was evaluated in macaques immunised with a vaccine composed of the most conserved regions of HIV‐1 and delivered by plasmid DNA, human adenovirus serotype 5, simian adenovirus serotype 63, MVA, Semliki Forest virus replicons and adjuvanted overlapping synthetic long peptides (SLP). We found that only the SLP formulation, but none of the genetic vaccine platforms induced antibodies recognizing linear HIVconsv epitopes, median 32/46 SLP.HIVconsv peptides. These antibodies bound to 15‐mer and SLP peptides, recombinant gp120 and trimeric gp140 of HIV‐1 Bal, YU2, JRFL and UG037, but failed to react with HIV‐1 Bal and IIIB virions and HIV‐1 Bal‐ and IIIB‐infected human cells, and consequently failed to induce neutralizing antibodies. Antibodies induced by the SLP.HIVconsv vaccination resulted in positive signals in routine HIV‐1 tests, an observation that provides important guidance for recruiting volunteers into future clinical trials.